Transformational university leadership : a case study for 21st century leaders and aspirational research universities - Coulson, Hilary L.; Zou, Yali; Fernandez, Frank (Great debates in higher education., 2022)
Universities are facing budget crises and growing competition, with many leaders clinging to older methods of leadership. This results in institutions with unprecedented deficits, decreased enrolments, and low graduation rates. What tools are necessary to succeed in the ever-changing and diversifying higher education market? In this book, the authors provide a model for leading universities in rapidly changing environments. Using the University of Houston as their case study, examining the institution's explosive growth under the transformative leadership of President Renu Khator and her team. The President's success in the realms of fundraising, organizational architecture, development, crisis management, and building campus culture are all facets of a revolutionary leadership model that can be replicated as a new style of academic governance. Transformational University Leadership presents a model of leadership for higher education institutions in the 21st century. With a special focus on gender and culture, the authors explore the leadership tactics and strategies university presidents use to uplift the University from a regional campus to a tier 1 research powerhouse. Offering strategies, anecdotes, and transferable methods for university leaders seeking to elevate their institution and thrive in the 21st century academic market.